2012
DOI: 10.2967/jnumed.112.105056
|View full text |Cite
|
Sign up to set email alerts
|

A Vaccinia Virus Encoding the Human Sodium Iodide Symporter Facilitates Long-Term Image Monitoring of Virotherapy and Targeted Radiotherapy of Pancreatic Cancer

Abstract: To assess therapeutic response and potential toxicity of oncolytic virotherapy, a noninvasive, deep-tissue imaging modality is needed. This study aimed to assess the feasibility, parameters, and determining factors of serial imaging and long-term monitoring of virotherapy and the therapeutic response of pancreatic cancer xenografts treated with a vaccinia virus carrying the human sodium iodide symporter GLV-1h153. Methods: Pancreatic cancer xenografts (PANC-1) in nude mice were treated systemically or intratum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…After 48 h, I − accumulation decreased, NIS was no longer detectable at the plasma membrane, and the cells were dying (128). Haddad and colleagues (129) sequentially imaged a pancreatic tumor infected with a VV encoding NIS. They monitored NIS expression using radiotracer accumulation and IHC in explanted tumors at different stages of infection, observing that cell death was linked to decreased I − uptake.…”
Section: Replication-competent Oncolytic Virusesmentioning
confidence: 99%
“…After 48 h, I − accumulation decreased, NIS was no longer detectable at the plasma membrane, and the cells were dying (128). Haddad and colleagues (129) sequentially imaged a pancreatic tumor infected with a VV encoding NIS. They monitored NIS expression using radiotracer accumulation and IHC in explanted tumors at different stages of infection, observing that cell death was linked to decreased I − uptake.…”
Section: Replication-competent Oncolytic Virusesmentioning
confidence: 99%
“…[5][6][7] Conditionally replicating viruses have been gaining increasing attention for their ability to kill tumor cells by oncolysis and apoptosis, and hence, this attenuated strain has shown promise as a selective anticancer agent. 5 We constructed a new virus which had three nonessential viral genes deleted and replaced with GFP, β-galactosidase, and the hNIS genes, creating GLV-1h153.…”
Section: Discussionmentioning
confidence: 99%
“…Several databases investigating genes associated with poxvirus infection have been established, such as the virus pathogen database and analysis resource (ViPR), 5 the poxvirus bioinformatics resource center, 6 the poxvirus proteomics database, 7 as well as literature addressing detection of and identification of different strains of orthopoxvirus. 1,[29][30][31][32] Although these databases were aimed mainly at the risk of bioterrorism or possible virus pandemic, information from these databases may be crucial to better understand virus behavior for oncotherapy.…”
mentioning
confidence: 99%
“…11 For these studies, we have modified the GLV-1h68 virus to carry hNIS, an imageable gene in an attempt to produce a therapeutic virus that we may be tracked by noninvasive imaging. We have previously published our success in utilizing this viral construct to both treat and provide real-time, non-invasive imaging of thyroid 12 , pancreatic 13 and triple negative breast cancer (TNBC) xenografts 14 . Most recently, we have demonstrated that GLV-1h153 can treat orthotopic TNBC underline tumors, prevent metastasis, and facilitate 131 I imaging of positive surgical margins after resection.…”
Section: Discussionmentioning
confidence: 99%